Analytical modeling and simulation of a CMOS-MEMS cantilever based CO2 sensor for medical applications - Mirza, A. (2013)
Capnometers measure the concentration of CO2 in exhaled breath which could prevent serious problems in all areas of healthcare, from pre-hospital to extended care, and everywhere in between. Presently, high cost, big size and high power usage limit the scope of the conventional capnometers and their adaption. To overcome these issues, a CMOS MEMS micro-cantilever has been proposed for capnometric applications. Analytical modeling and simulation of the microcantilever sensor is carried out to determine its resonance frequency and sensitivity. According to the developed analytical model and simulation results, the sensor has 1 difference in the resonance frequency. The sensitivity of the sensor is determined analytically at different thicknesses of the polymer coating layer. The sensitivity of the sensor is 3.18 Hz/100ppm at 5 Î¼m polymer layer thickness. Â© 2013 IEEE.